MATTHEW H. VAN DAM & CHARLES W. O’BRIEN (2015) Review of the genus Miloderes Casey, 1888 (Coleoptera: Curculionidae: Entiminae), with desciptions of three new species. Zootaxa, 4006 (2): 247–284. - Dam, Matthew H. Van; O’brien, Charles W. (Zootaxa, 2016)
N/A